Spatial Analysis of Aids and the Social Determinants of Health [Análise Espacial Da Aids E Os Determinantes Sociais de Saúde] - De Sousa-Paiva, S (Assocaicao Brasileira de Pos, Gradacao em Saude Coletiva, 2019)
Introduction: The social determinants of health (SDH) are factors that can influence the distribution of rates for acquired immunodeficiency syndrome (AIDS) in a given region. The objective of this study was to analyze SDHs related to AIDS. Method: Ecological study, using spatial analyses techniques. 7,896 disease case reports were analyzed over a period of 11 years. Subjects were 13 years or older and residents of the state of Ceará, in the northeast of Brazil. The area of analysis was the municipality, calculating both the average rate of AIDS and the Freeman-Tukey transformed average rate for measuring softening. We used the Simple Linear Regression Model to make the spatial correlation between AIDS detection rates and SDH. A Geographic Information Systems (GIS) was used to manipulate georeferenced data. Results: High rates of AIDS could be found in cities with better living conditions. Additionally, there was a significant relationship between primary health care coverage and lower rates of the disease in Ceará. Conclusion: Socioeconomic indicators with statistically significant correlation to the distribution of AIDS should be targeted by strategies policies in the fight against the disease. © 2019 Associação Brasileira de Saúde Coletiva.
Keywords: Acquired Immunodeficiency Syndrome; Social determinants of health; Spatial analysis